Biomechanical aspects of axonal damage in glaucoma: A brief review. (April 2017) - ; Dowling, John E.; Downs, Crawford; Ellisman, Mark H.; Fisher, Steven; Fortune, Brad; Fruttiger, Marcus; Jakobs, Tatjana; Lewis, Geoffrey; Masland, Richard H.; Mitchell, Claire H.; Morrison, John; et al.
Abstract: The biomechanical environment within the optic nerve head (ONH) is complex and is likely directly involved in the loss of retinal ganglion cells (RGCs) in glaucoma. Unfortunately, our understanding of this process is poor. Here we describe factors that influence ONH biomechanics, including ONH connective tissue microarchitecture and anatomy; intraocular pressure (IOP); and cerebrospinal fluid pressure (CSFp). We note that connective tissue factors can vary significantly from one individual to the next, as well as regionally within an eye, and that the understanding of ONH biomechanics is hindered by anatomical differences between small-animal models of glaucoma (rats and mice) and humans. Other challenges of using animal models of glaucoma to study the role of biomechanics include the complexity of assessing the degree of glaucomatous progression; and inadequate tools for monitoring and consistently elevating IOP in animal models. We conclude with a consideration of important open research questions/challenges in this area, including: (i) Creating a systems biology description of the ONH; (ii) addressing the role of astrocyte connective tissue remodeling and reactivity in glaucoma; (iii) providing a better characterization of ONH astrocytes and non-astrocytic constituent cells; (iv) better understanding the role of ONH astrocyte phagocytosis, proliferation and death; (v) collecting gene expression and phenotype data on a larger, more coordinated scale; and (vi) developing an implantable IOP sensor. Highlights: This review article summarizes the results of a discussion that occurred at the March 2015 Lasker/IRRF Initiative for Innovation in Vision Science conference on Astrocytes and Glaucomatous Neurodegeneration. Challenges, open questions, and new tools to address these questions are summarized